Determination of the Association between Background Characteristics of Slaughterhouse Workers and Their Personal Hygiene Knowledge on Meat Handling Tamala - Asare, Solomon Ossom; Abiodun, Ogwa Oluwafunmike; Omanchi, Emmanuel Olofu; Yeboah, Genevieve Akpah; Maxwell, Laweh Addo (Darul Yasin Al Sys, 2025)
According to the Food and Agriculture Organization (FAO) of the United Nations, meat products, either in fresh or frozen conditions, very rapidly become highly susceptible to microbial contamination as soon as they are exposed. It is exactly this situation that makes the hygiene of meat processing very relevant, this make it reasonable that the determination of the association between background characteristics of slaughterhouse workers and their personal hygiene knowledge on meat handling as paramount. This current study, therefore, assessed butchers’ characteristic knowledge and perception of good hygiene as storage practices through a cattle slaughterhouse case analysis. Content validation was utilised to authenticate the questionnaire items, which were administered face-to-face to the respondents (i.e., the butchers). The questionnaire included questions. The results showed that the slaughterhouse workers were male (Freq. = 100%, n = 50), acquired formal education with Low Personal Hygiene Knowledge is about 61%, no formal education 16 % while those with High Personal Hygiene Knowledge for those with formal education is 16% and no formal education is 7% at n = 41), and were strongly (p < 0.0001) familiar with good hygiene knowledge practices. The educated butchers provided good examples that demonstrated knowledge and perception aspects of good hygiene within the age 20-30yrs. When compared to those at the age of 31yrs to 40yrs. Very conscious of their knowledge and perception of good hygiene characterization herein have to strive for continuous improvement in their slaughterhouse activities to assure beef quality and consumer safety.